2016
DOI: 10.1590/0034-737x201663010010
|View full text |Cite
|
Sign up to set email alerts
|

Adubação potássica aplicada na axila foliar e no solo em coqueiro anão verde

Abstract: Application of soil and foliar potassium to green dwarfish coconut treeThe influence of doses of KCl applied via soil and via leaf axil on the leaf nutrient concentration in green dwarf coconut tree (Cocos nucifera L.) was evaluated. The experiment was conducted in a commercial orchard in Campos dos Goytacazes, Brazil, in a Typic Quartzipsamments, from May 31, 2007 to May 31, 2008, using a randomized complete block design with five treatments and sixteen replicates. Treatments consisted of two application mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…Over the years, leaf K concentration in the absence of KCl decreased, due to the depressive effects of TSP and MgO on K nutrition, mainly in the absence of P fertilization (Figure 2c). In green dwarf coconut palm, K concentrations also increased in the leaves (SILVA et al, 2009;RIBEIRO et al, 2016) and in the water and in fruit peel, due to K fertilization (RIBEIRO et al, 2011). In Rio Grande do Norte State, leaf K concentrations showed a high correlation with the number of fruits in the sixth year of cultivation of green dwarf coconut tree (FERREIRA NETO et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, leaf K concentration in the absence of KCl decreased, due to the depressive effects of TSP and MgO on K nutrition, mainly in the absence of P fertilization (Figure 2c). In green dwarf coconut palm, K concentrations also increased in the leaves (SILVA et al, 2009;RIBEIRO et al, 2016) and in the water and in fruit peel, due to K fertilization (RIBEIRO et al, 2011). In Rio Grande do Norte State, leaf K concentrations showed a high correlation with the number of fruits in the sixth year of cultivation of green dwarf coconut tree (FERREIRA NETO et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although soil fertility is not a limiting factor for coconut palm, fertilization greatly affects its yield (SOBRAL, 1998;SILVA et al, 2006;SILVA et al, 2009). Coconut trees have continuous growth, demanding large amounts of soil nutrients (RIBEIRO et al, 2016) that must be replenished by fertilization. Studies carried out in Brazil have evaluated mainly the response of coconut palm to N and K fertilization (SILVA et al, 2006;SILVA et al, 2009;RIBEIRO et al, 2011), but not to P and Mg applications.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to meet the nutritional requirements, the supply of nutrient in adequate portions is one of the greatest difficulties faced by the coconut producers (Ferreira Neto et al, 2007b. Regarding coconut yield, there are innumerous studies highlighting the potential of potassium fertilization in the increment of plant growth and production (Sobral & Nogueira, 2008;Silva et al, 2009;Ferreira Neto et al, 2014;Ribeiro et al, 2016). Thus, this study aimed to evaluate the influence of potassium sulfate doses applied via soil on the growth and production of green dwarf coconut (C. nucifera L.) cultivated in saline-sodic soil.…”
Section: R E S U M Omentioning
confidence: 99%
“…Teixeira et al (2005) report the importance of the supply of N, P and K in the dwarf coconut crop to increase the mean contents of K in the leaf tissue, and observed that for every 100 kg of K 2 O plant -1 year (Sobral & Nogueira, 2008;Silva et al, 2009;Ribeiro et al, 2011Ribeiro et al, , 2016, this is due to the conditions of salinity and sodicity of the soil, besides the young conditions of the plants and their small size, since they are in the third year of cultivation. However, the effects of potassium fertilization on the increment in the number of fruits per plant are mainly observed from the 6 th year of cultivation of the green dwarf coconut (Ferreira Neto et al, 2007b).…”
Section: Ementioning
confidence: 99%
See 1 more Smart Citation